Electrocatalytic Oxidation of Glycerol Using Solid‐State Synthesised Nickel Boride: Impact of Key Electrolysis Parameters on Product Selectivity. Issue 12 (22nd June 2021) - Brix, Ann Cathrin; Morales, Dulce M.; Braun, Michael; Jambrec, Daliborka; Junqueira, João R. C.; Cychy, Steffen; Seisel, Sabine; Masa, Justus; Muhler, Martin; Andronescu, Corina; Schuhmann, Wolfgang
Abstract: Water electrolysis is a promising technology for sustainable hydrogen production; however, its commercialisation is limited by sluggish kinetics of the oxygen evolution reaction (OER). A potential alternative to the OER is hence required and is seen in the electrocatalytic glycerol oxidation reaction (GOR) as it offers concomitant value‐added product generation from a cheap and abundant feedstock. Here, we show a facile solid‐state synthesis method to obtain Ni‐boride, a non‐noble metal‐based catalyst subsequently used in an in‐depth study of the GOR product distribution as a function of key electrolysis parameters. Highly crystalline, mixed‐phase Ni borides were obtained, and their synthesis was successfully optimised regarding GOR activity. Long‐term chronoamperometry was conducted in a circular flow‐through cell and samples were analysed by HPLC. It is shown that the formation of lactic acid, one of the most valuable GOR products, can be enhanced by optimising the electrolyte composition and the applied potential. Abstract : To make H2 production via sustainable water electrolysis technology economically feasible, the oxygen evolution reaction may be replaced for e. g. by converting glycerol from a biodiesel waste stream into valuable products. The non‐noble metal‐based electrocatalyst Ni boride obtained easily via a scalable solid‐state synthesis is used together with optimized electrolysis parameters to tune the selectivity to favour valuable products such as lactic acid.